(untitled) (Development Service Industry Management, 2024)
The integration of Ukraine into the world economic system requires additional measures regarding the competitiveness of domestic enterprises on the domestic and foreign markets. According to the Law of Ukraine "On Basic Principles and Requirements for the Safety and Quality of Food Products" (No. 771/97-BP dated 23.12.1997, as amended), enterprises engaged in the production and distribution of food products must apply HACCP or other safety and quality assurance systems during the production and circulation of food products. Implementation of HACCP at all enterprises of the food industry is foreseen. This also applies to restaurants. In September 2016, Chapter VII of the Law "On Basic Principles and Requirements for the Safety and Quality of Food Products" entered into force, according to which the HACCP system must be implemented by September 20, 2019 by all enterprises that produce, store, transport and sell food products . During the development and implementation of permanent procedures based on the principles of the hazard analysis and critical control point system (HACSR - Hazard Analysis and Critical Control Point), the restaurant industry faces a number of problems related to external factors (imperfect legal framework, lack of information), as well as internal (lack of special knowledge, incompetence and resistance of personnel). This forces enterprises to completely transfer the development of the system or to purchase ready-made HACCP documentation from third-party organizations, which increases the number of institutions where the HACCP system formally exists. Common difficulties are associated with the correct analysis of dangerous factors and the establishment of adequate control measures for them. The introduction in Ukraine of international standards for the quality of hotel services, as well as the quality and safety of culinary products of restaurant establishments, directly affects all enterprises in the field of hospitality. Despite the fact that a number of domestic hotel enterprises and restaurant establishments have already reached the level of international standards of service quality and restaurant product safety, many issues remain insufficiently disclosed and understood by market participants, especially in the HACCP food safety management system. So, for example, the processes of analyzing risks and dangerous factors in the technological processes of storage and production of culinary products and assessing the probability of their occurrence need more detailed explanations in order to establish rational control measures for restaurant enterprises.